Endophytic Fungal Consortia Enhance Basal Drought-Tolerance in Moringa oleifera by Upregulating the Antioxidant Enzyme (APX) through Heat Shock Factors - Javeria Javed; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Humaira Gul; Aziz Ud-Din; Jalal Ud-Din; Mohammad Sohail; Muhammad Mizanur Rahman; In-Jung Lee (MDPI AG, 2022)
Global climate change has imposed harsh environmental conditions such as drought. Naturally, the most compatible fungal consortia operate synergistically to enhance plant growth and ecophysiological responses against abiotic strains. Yet, little is known about the interactions between phytohormone-producing endophytic fungal symbionts and plant growth under drought stress. The existing research was rationalized to recognize the role of newly isolated drought-resistant, antioxidant-rich endophytic fungal consortia hosting a xerophytic plant, Carthamus oxycantha L., inoculated to Moringa oleifera L. grown under drought stress of 8% PEG (polyethylene glycol-8000). Under drought stress, the combined inoculation of endophytic strain Microdochium majus (WA), Meyerozyma guilliermondi (TG), and Aspergillus aculeatus (TL3) exhibited a significant improvement in growth attributes such as shoot fresh weight (1.71-fold), shoot length (0.86-fold), root length (0.65-fold), dry weight (2.18-fold), total chlorophyll (0.46-fold), and carotenoids (0.87-fold) in comparison to control (8% PEG). Primary and secondary metabolites were also increased in M. oleifera inoculated with endophytic consortia, under drought stress, such as proteins (1.3-fold), sugars (0.58-fold), lipids (0.41-fold), phenols (0.36-fold), flavonoids (0.52-fold), proline (0.6-fold), indole acetic acid (IAA) (4.5-fold), gibberellic acid (GA) (0.7-fold), salicylic acid (SA) (0.8-fold), ascorbic acid (ASA) (1.85-fold), while abscisic acid (ABA) level was decreased (−0.61-fold) in comparison to the control (8% PEG). Under drought stress, combined inoculation (WA, TG, TL3) also promoted the antioxidant activities of enzymes such as ascorbate peroxidase (APX) (3.5-fold), catalase (CAT) activity (1.7-fold), and increased the total antioxidant capacity (TAC) (0.78-fold) with reduced reactive oxygen species (ROS) such as H2O2 production (−0.4-fold), compared to control (8% PEG), and stomatal aperture was larger (3.5-fold) with a lesser decrease (−0.02-fold) in water potential. Moreover, combined inoculation (WA, TG, TL3) up regulated the expression of MolHSF3, MolHSF19, and MolAPX genes in M. oleifera under drought stress, compared to the control (8% PEG), is suggestive of an important regulatory role for drought stress tolerance governed by fungal endophytes. The current research supports the exploitation of the compatible endophytic fungi for establishing the tripartite mutualistic symbiosis in M. oleifera to alleviate the adverse effects of drought stress through strong antioxidant activities.